Pengaruh Penerapan Powerpoint terhadap Hasil Belajar pada Pembelajaran Tematik untuk Siswa Kelas III Sekolah Dasar Negeri 11 Pontianak Timur - Juliet Nanda Kartika; Hamdani Hamdani; Asmayani Salimi; Rio Pranata (Journal on Education, 2024)
This research aims to analyze the effect of applying PowerPoint on learning outcomes in thematic learning for class III students at Elementary School 11 East Pontianak. The research method used is experimentation in the form of quasi experimental design. The research population was 27 students in class III A and 27 students in class III B. The data collection technique used is a measurement technique and the data collection tool is a test in the form of an essay with 12 questions. Based on data analysis, the average final test for the experimental class = 66.27 and the average for the final test for the control class = 54.8. The results of hypothesis testing using the t-test obtained tcount = 7.86621, while dk (27+27-2 =52) with the level (α = 5%) obtained ttable = 0.6840, which means tcount > ttable. So Ha accepted. Based on the results of the effect size (ES) calculation, the ES value = 1.85. Thus it can be concluded that the application of PowerPoint in thematic learning has an influence on the learning outcomes of class III students at State Elementary School 11 East Pontianak by 96%.